Interruption of the Right Pulmonary Artery in a Neonate - Mohammadreza Khalilian; Taraneh Faghihi Langroudi; Ali Dabbagh; Ramin Baghaei Tehrani; Tahmineh Tahouri (Case Reports in Cardiology)
Interruption of the right pulmonary artery is a very rare anomaly which can be associated with other congenital heart lesions or can occur in isolation. Clinical presentations of the unilateral interruption of a pulmonary artery are varied including pulmonary hypertension, recurrent infection, dyspnea, exercise intolerance, hemoptysis, and chest pain. Less commonly, patients may be asymptomatic. Diagnosis of this anomaly is made by echocardiography and CT angiography as well as cardiac MRI. Treatment options are medical versus surgical management and often recommended in symptomatic patients with pulmonary hypertension, recurrent infection, and hemoptysis. Herein, we describe a very rare case of right pulmonary artery originating from the right subclavian artery in a 12-day-old neonate.